Evaluation of trimethylamine n-oxide levels in pleural effusion - Aydin, Siyami; Cakmak, Muharrem; Gursu, Mehmet Ferit; Kaymaz, Tugce (Bayrakol Medical Publisher, 2023)
Aim: Although many parameters have been studied for the diagnosis, follow-up and treatment of pleural fluid, the level of Trimethylamine-N oxide (TMAO) has not been reported so far. In our study, by investigating the TMAO levels in the effusion fluid of patients with pleural effusion, we aimed to report a mean pleural fluid TMAO value and its relationship with diseases. Material and Methods: The pleural fluids of 49 patients who were treated in the last year were included in the study. The patients were divided into two groups as transudate (Group 1) and exudate (Group 2) and the results were compared. Results: The mean age of the patients was 65.77 +/- 15.13 years. The mean TMAO value of the patients was found to be 0.43 +/- 0.12, which is lower than normal TMAO plasma values. When groups 1 and 2 were compared, the results of Group 1 were found to be significant in terms of the mean PLT and CRP values (p < 0.05). Although trimethylamine-N oxide concentrations were low in normal plasma, no significant difference was found when the two groups were compared (p = 0.9124). Discussion: Although the serum Trimethylamine-N oxide levels of the patients were reported to be high for most of these reasons, no elevation of TMAO was observed in the pleural effusion fluids of the disease groups in our study. On the contrary, a mean value well below the serum TMAO values of these patients was obtained. The pleural fluid TMAO value was determined as 0.43 +/- 0.12. We are of the opinion that even if the serum TMAO values that cause pleural effusion are high in the disease groups, this elevation does not pass into the pleural space.
Keywords: Effusion; Pleura; Trimethylamine-N oxide